Tasawuf Nusantara (Studi Tentang Nilai-Nilai Mistis dalam Agama Sunda Wiwitan di Kampung Pasir Samarang Garut) - Enok Risdayah (Syifa al-Qulub, 2019)
Local religion in Indonesia is actually a form of pluralism that should be protected, because religion is part of human rights. Although many experienced challenges and obstacles, they were recognized and not officially recognized by the state, but the adherents of the local religion to this time still exist and they proved to be able to survive. On the other hand the flow of global life hit all sides of human life including religion. Modern life has almost permeated allatheapeople of theaworld with theiglitter ofimaterialism. Inithisicondition Sufism is present as an antidote to soothing and purifying the mind, but not as a place of escape. Sufism teaches various things about how humans should behave, acting to achieve the ultimate goal, namely the pleasure of God. The problem is whether in local religion there are Sufism values, and how those values are applied in daily life. Thisdstudyauses qualitativetmethodsqwith interviewsiandgliterature as the data collection technique. Thefresultsdofjjtheggstudyccshowdthat therediare Sufism values in Sundanese Wiwitan religion as a local religion in the archipelago that can be applied inqdailydlife, onesof whicheeisaby always refraining from doing evil, instilling compassion with fellow humans.